LESSON STUDY KOLABORATIF SEBAGAI UPAYA PENINGKATAN PROFESIONALITAS GURU DALAM PELAKSANAAN PENILAIAN AUTENTIK - Ribut Wahyu Eriyanti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Teachers must have pedagogic, professional, personal and social competencies. In fact, some teachers still do not have these competencies. Collaborative lesson study is carried out to develop teacher professionalism, especially in carrying out authentic assessments. The results showed that through collaborative lesson study the professionalism of teachers in carrying out authentic assessments increased. In terms of pedagogic, teachers are able to carry out assessment and evaluation of learning processes and outcomes, able to utilize the results of assessment and evaluation for learning, take reflective actions to improve quality learning. In terms of personality, the teacher is able to respect students objectively and fairly, honestly, firmly, and humanely in carrying out assessments, demonstrating work ethic, high responsibility in carrying out assessments. From a social perspective, the teacher is able to act objectively, be fair, communicate with students and colleagues, and be able to introspect. In terms of professionals, the teacher is able to describe competencies into thesubstance of the assessment material appropriately.Keywords: lesson study, assessment, evaluation, learning, professional